Molar e molecular: o pensamento como ato criativo em Gilles Deleuze - Martins, Caio Felipe Varela (2017)
With the term multiplicity, Deleuze and Guattari reach a different space from philosophical knowledge by affirming difference rather than denying it. We present in the present work a research through the cartographic method in the sense of approaching some concepts placed as main to map the movement of thought in the deleuzo-guattarian philosophy. The terms: molar and molecular will guide our research as the presentation of the movement itself by the authors, their exchanges and mutations not only in thought but in reality itself shows us a coexistent duality that also shows us multiplicity, heterogeneity and movement. This movement of thought will lead us to the path of finding the act of creation, and more specifically the creation of concepts as the main exercise of the philosopher.